2013
DOI: 10.1021/ma400608q
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Branch Incorporation into the Lamella Crystal on the Crystallization Behavior of Polyethylene with Precisely Spaced Branches

Abstract: Depending on the degree of short chain branch (SCB) incorporation, the crystallization behavior and resultant crystalline structure drastically change in polyethylene with precisely spaced branches. In polyethylene with hexyl branches precisely spaced on every 21st carbon (HB21), only crystallization mediated by a transient hexagonal phase without incorporation of the SCB was observed. On the other hand, in polyethylene with ethyl branches precisely spaced on every 21st carbon (EB21), crystallization behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
38
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 30 publications
4
38
1
Order By: Relevance
“…At slightly higher crystallization temperatures (10–15 °C), the transient hexagonal mesophase forms and subsequently thins or thickens to include zero or one short‐chain branch (SCB). The folded chains simultaneously adopt the trans‐conformation and slide past one another in the mesophase to reach one of two new equilibrium lamellar thicknesses, the thicker of these measuring about 56 Å (approximately the length of two –(CH 2 ) 20 – units) and the thinner one of about 25 Å (approximately the length of one –(CH 2 ) 20 – unit) . Thus, Et‐21 crystallized isothermally between 10 and 15 °C exhibits lamellae of two thicknesses.…”
Section: Alkyl‐branched Admet–polyethylenementioning
confidence: 96%
See 4 more Smart Citations
“…At slightly higher crystallization temperatures (10–15 °C), the transient hexagonal mesophase forms and subsequently thins or thickens to include zero or one short‐chain branch (SCB). The folded chains simultaneously adopt the trans‐conformation and slide past one another in the mesophase to reach one of two new equilibrium lamellar thicknesses, the thicker of these measuring about 56 Å (approximately the length of two –(CH 2 ) 20 – units) and the thinner one of about 25 Å (approximately the length of one –(CH 2 ) 20 – unit) . Thus, Et‐21 crystallized isothermally between 10 and 15 °C exhibits lamellae of two thicknesses.…”
Section: Alkyl‐branched Admet–polyethylenementioning
confidence: 96%
“…In metallocene PE, which contains random branching, Mirabella found that the longer ethylene sequences crystallize before the shorter sequences, forming thick orthorhombic crystals composed of the longer ethylene sequences, with the shorter run lengths remaining in the amorphous phase. Conversely, in precisely branched PE, all run lengths are the same without long sequences to crystallize rapidly at higher temperatures, thereby allowing a transient hexagonal mesophase to form and persist long enough for the formation of energetically stable crystals …”
Section: Alkyl‐branched Admet–polyethylenementioning
confidence: 99%
See 3 more Smart Citations